Pengaruh Work Life Balance Dan Pengembangan Karir Terhadap Kinerja Karyawan Dengan Keterlibatan Kerja Karyawan Sebagai Variabel Intervening (Studi Kasus Apoteker Dan Tenaga Teknis Kefarmasian Di Rumah Sakit Umum Bunda Medical Center Padang) - Muhammad Alvhito Fernandes; Vivi Nila Sari; Chintya Ones Charli (CV. ITTC INDONESIA, 2026)
This study aims to find out how much work-life balance and career development influence employee performance, with employee engagement as an intervening variable, among Pharmacists and Pharmacy Technical Staff at Bunda Medical Center General Hospital in Padang. Data was collected through a survey by distributing questionnaires to 48 respondents consisting of pharmacists and pharmacy staff. The analysis method used was path analysis with SmartPLS. The results based on partial tests show that work-life balance does not have a significant effect on employee engagement. Career development has a significant effect on employee engagement. Work-life balance does not have a significant effect on employee performance. Career development has a significant effect on employee performance. There is a significant effect of engagement